Responding to banana xanthomonas wilt amidst multiple pathogens and pests - Mwangi, M. (2007)
Xanthomonas wilt (BXW) is the most serious threat to sustainable banana production in East and Central Africa. Before the advent of BXW major biotic constraints were black leaf streak (Sigatoka), Fusarium wilt, bunchy top and streak viruses, weevils and nematodes. The rapid spread of BXW has diverted attention from the other biotic constraints, which, unlike BXW, rarely cause total yield loss. In addition, there are resistant varieties for most biotic constraints of banana, but not for BXW. Although in C3P the focus is on BXW, the pest complexes in the region cannot be overlooked, as they are on the same crop and system. There are interactive effects between pests and pathogens that must be managed for successful rehabilitation of banana production, while extension messages need to be well developed to communicate clearly on numerous biotic constraints. The multiplicity of pests also demands increased investments in technical capacity to improve diagnosis and ensure responses are timely and appropriate. With little extra effort, measures targeting BXW can also contribute to management of other biotic constraints. For example, the provision of clean planting material would in one stroke limit spread of several pathogens and pests that are potentially transmitted through infected suckers. This brief highlights areas of convergence in management BXW and other key biotic constraints facing farmers in East and central Africa. RESPONDING TO BANANA XANTHOMONAS WILT AMIDST MULTIPLE PATHOGENS AND PESTS (PDF Download Available). Available from: https:www.researchgate.netpublication303493669_RESPONDING_TO_BANANA_XANTHOMONAS_WILT_AMIDST_MULTIPLE_PATHOGENS_AND_PESTS [accessed Jan 19 2018].